(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Optical fibers till date are the highest data capacity supported network. The bandwidth supported by fibers is very high but deploying fibers in many cases is not possible. In this scenario the alternate approach that can carry same data rate is FSO (Free space optics) but FSO link can not support a long distance transmission because FSO links are affected by the atmospheric conditions adversely. To increase the link distance of FSO, optical amplification of signal can be done. In this paper use of SOA (Semiconductor optical amplifier) as preamplifier is presented, performance of free space optical system is investigated with varying number of channels and with varying channel spacing. With 8 channels, 10 dBm input power the link range is 6.5 Km, for 16 channels it is 5.1 Kms. Investigation on bit rate and receiver sensitivity is also done. Maximum bit rate achieved with WDM system is 10 Gbps and receiver sensitivity with varying bit rate values are analyzed and found that receiver is most sensitive with 2.5 Gbps.